Health Education and Therapeutic Group Therapy Pregnant Women as a Prevention of Stunting Risk Factors - Nugraha, M. Akbar; Keliat, Budi Anna; Mustikasari, Mustikasari (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Early intervention during pregnancy can prevent stunting. Pregnant women can prevent stunting by addressing risk factors such as nutrition during pregnancy, infection during pregnancy, and depression during pregnancy. This study was designed to identify the effect of health education and therapeutic group therapy on preventing stunting risk factors. Method: The research design was quasi-experimental with a control group. The groups in this study were divided into two groups, the offline group, consisting of two groups: the intervention group that received offline health education and the group that received offline health education and therapeutic group therapy. The online group consisted of three groups, the intervention group that received online health education, the group that received online health education and therapeutic group therapy, and the control group that refused to receive health education and therapeutic group therapy interventions but was sent leaflets on improving development in pregnant women. The study was conducted offline and online. The sample consisted of 157 pregnant women and husbands, 64 women and husbands offline, and 93 women and husbands online. The instruments in this study were questionnaires consisting of demographic data of pregnant women and husbands, nutritional data during pregnancy (upper arm circumference (LiLA) and haemoglobin, depression during pregnancy with the EPDS questionnaire, Data analysis used univariate and bivariate frequency distribution, central tendency, and paired t-test. The results showed that upper arm circumference (LiLA) and Hb did not show significant differences between the intervention and control groups. Health education and offline therapeutic group therapy significantly decreased the risk factors for stunting and depression during pregnancy. Health education and therapeutic group therapy are recommended to be carried out in health service settings, both offline and online, as a form of mental health services for pregnant women in preventing risk factors for stunting.